Quantum rotors in Pca21 lattice - Freiman, Yu.A.; Grechnev, Alexei (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Analytical calculations of the potential barrier hindering rotation of the hydrogen molecules in the molecular field of neighboring molecules are performed for molecular solid hydrogen. The calculations are made for the four-sublattice Pca21 lattice which minimizes the electrostatic energy of classical quadrupoles on an hcp lattice.